2002
DOI: 10.1093/jurban/79.3.383
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Follow-up of Survivors of a Mass Shooting Episode

Abstract: This report describes a 3-year follow-up study of survivors of a mass shooting incident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 16 publications
4
55
0
Order By: Relevance
“…In our study, health problems (as evaluated in the first survey) were not a clear determinant of response in the second wave for the overall affected population (residents and emergency workers). In nine out of twelve previous disaster studies, posttraumatic stress symptoms or disorder [11,13,14,[16][17][18]20] or other psychological symptoms such as anxiety and depression [11,12,15] at the first wave were not predictors of loss to follow up. However, the presence of predisaster depression [9], pre-disaster behavioral and emotional problems [21] and a higher level of general psychological distress at the first wave [20] were associated with lower participation rates at the second wave of the study.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In our study, health problems (as evaluated in the first survey) were not a clear determinant of response in the second wave for the overall affected population (residents and emergency workers). In nine out of twelve previous disaster studies, posttraumatic stress symptoms or disorder [11,13,14,[16][17][18]20] or other psychological symptoms such as anxiety and depression [11,12,15] at the first wave were not predictors of loss to follow up. However, the presence of predisaster depression [9], pre-disaster behavioral and emotional problems [21] and a higher level of general psychological distress at the first wave [20] were associated with lower participation rates at the second wave of the study.…”
Section: Discussionmentioning
confidence: 80%
“…In some studies after disasters non-responders were more likely to be male and never married, and have a lower household income than responders [9][10][11], while other studies did not find a difference between responders and non-responders in these demographic factors [12][13][14][15][16][17][18]. The same diversity in results was observed for health-related factors.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…If claimants in litigation show lower remission rates, it could be because they are focusing on the litigation and the need to appear "damaged" (Bryant and Harvey 2003 ). It is noted that delay in onset of PTSD is quite rare (North et al 2002 ) so that it may arise from compensation motivation.…”
Section: Prevalencementioning
confidence: 99%
“…[10], Schlenger et al [11], Silver et al [12]) have examined the mental health consequences of major terrorist attacks experienced in the United States (i.e., Oklahoma City bombing, the World Trade Center, the Pentagon, and the anthrax attacks in 2002-2003). As a whole, the studies revealed that the effects from acts of terrorism on mental health affected a higher percentage of people and that the effects were more enduring than the negative psychological outcomes reported in previous studies for natural or accidental disaster survivors.…”
Section: Lessons From Terrorist Attacksmentioning
confidence: 99%